Type III Secretion: Building and Operating a Remarkable Nanomachine. Issue 2 (February 2016) - Portaliou, Athina G.; Tsolis, Konstantinos C.; Loos, Maria S.; Zorzini, Valentina; Economou, Anastassios
Abstract : The Type III secretion system (T3SS) is a protein export pathway that is widespread in Gram-negative bacteria and delivers effector proteins directly into eukaryotic cells. At its core lie the injectisome (a sophisticated transmembrane secretion apparatus) and a complex network of specialized chaperones that target secretory proteins to the antechamber of the injectisome. The assembly of the system, and the subsequent secretion of proteins through it, undergo fine-tuned, hierarchical regulation. Here, we present the current understanding of the injectisome assembly process, secretion hierarchy, and the role of chaperones. We discuss these events in light of available structural and biochemical dissection and propose future directions essential to revealing mechanistic insight into this fascinating nanomachine. Trends: The type III secretion system (T3SS) is essential for bacterial pathogenesis, symbiosis, and motility. At its core, the T3SS contains a complex injectisome, built of >20 proteins that need to be properly assembled into a functional unit. Injectisome biogenesis and T3S undergo sophisticated, multistepped regulation. Elucidating the molecular mechanism of T3S stands to benefit from in vitro assays to mechanistically dissect the process.